PENGARUH TRANSCUTOL P DAN PEG 400 DALAM PEMBUATAN TABLET LIQUISOLID NIFEDIPIN TERHADAP MUTU FISIK DAN DISOLUSI - Kuncahyo, Ilham; Hutami, Shabrina Nindya; Wulandari, RR Sri (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2025)
Nifedipine as a hypertension drug has the problem of low solubility (BCS class II), leading to decreased dissolution and bioavailability. Formulation of nifedipine liquisolid using non-volatile solvents can overcome this problem. This study aimed to evaluate the effect of Transcutol P and PEG 400 as non-volatile liquisolid ingredients on the physical quality and dissolution of nifedipine liquisolid tablets. This study used seven nifedipine liquisolid formulations, each with varying concentrations of Transcutol P or PEG 400 as non-volatile solvents and lactose as carrier material. Formula 1 (20% Transcutol: 80% lactose), Formula 2 (25% Transcutol: 75% lactose), Formula 3 (30% Transcutol: 70% lactose), Formula 4 (20% PEG 400: 80% lactose), Formula 5 (25% PEG 400: 75% lactose), Formula 6 (30% PEG 400: 70% lactose), and one control formula. The nifedipine liquid produced from each formula was forged into tablets using the direct felting method with a weight of approximately 200 mg. The tablets were tested for physical quality and dissolution, and the results were statistically analyzed using SPSS version 12.0. The results showed that Transcutol P and PEG 400 as liquisolid ingredients for nifedipine tablets provided good physical quality and improved the quantity and rate of drug release. The effect of PEG 400 as a liquisolid material for nifedipine tablets slowed down the disintegration time and accelerated the dissolution rate compared with Transcutol P. The dissolution profile showed that the release of nifedipine tablets with PEG 400 liquisolid material reached 30% at the fifth minute, meeting the requirements according to Indonesian Pharmacopoeia VI, which stipulates that more than 75% should be released at the sixtieth minute